Novel miniature pressure and temperature optical fibre sensor based on an extrinsic Fabry-Perot Interferometer (EFPI) and Fibre Bragg Gratings (FBG) for the ocean environment - Duraibabu, DineshBabu Babu; Poeggel, Sven; Omerdic, Edin; Kalli, Kyriacos; Capocci, Romano; Lacraz, Amédéé; Dooly, Gerard; Lewis, Elfred; Newe, Thomas; Leen, Gabriel; Toal, D. J F (My University, 2014)
A novel miniature sensor is proposed for accurate measurement of pressure (depth) and temperature changes in the ocean environment. The sensor is based on an optical fibre extrinsic Fabry Perot interferometer (EFPI) combined with a Fibre Bragg Grating (FBG). The EFPI provides pressure measurements while the Fibre Bragg Grating (FBG) provides temperature measurements. The FGB is post-inscribed into the EFPI using a femtosecond laser. The sensor is mechanically robust, corrosion resistant and suitable for use underwater. The combined pressure and temperature sensor system was mounted on-board a mini remotely operated underwater vehicle (ROV) in order to monitor the pressure changes at varying depths and compare with the reference pressure-depth sensor. The reflected optical spectrum of the sensor was monitored online and a pressure change caused a corresponding observable shift in the optical spectrum. The sensor exhibited excellent stability when measured over a 2 hour period underwater and its performance is compared with a commercially available reference sensor also mounted on the ROV. The comparison illustrates that the EFPI/FBG sensor is more accurate (∼0.025m) with a resolution of ∼0.005m, when compared to the reference sensor.
Keywords: FBG; Femtosecond laser; OFPTS; Pressure sensor; ROV